The environmental, economic and social repercussions of the cultivation of cannabis in the Ghafsay region - bousfiha, Sabah (Journal of Humanities & Social Sciences, 2020)
The study aims at highlighting the impact of Indian cannabis cultivation on the economic and social development and change of rural peasant life while affecting the environmental system in the region of Gefasai.To approach this subject in academic terms. We have built on the feminist approach, because it is important to highlight the different relationships and interactions between the poverty of the field (Gefasai) and its limited potential, on the one hand, and the rise of demographic growth, which has doubled the increasing needs of the village human being on the other, and the resulting environmental imbalances.We have also found the most important findings and recommendations in this study, which we include as follows: - the grain area between 2014 and 2017 has been reduced by more than 4,000 hectares per year, and is offset by Indian cannabis cultivation.The development of the annual income of farmers; He moved from 7,500 DHS per year before agriculture to 4,2333 DHS after agriculture.- the absolute poverty rate, which was 33% before agriculture, fell from 44% to 17% in 2017.- the proportion of job opportunities developed from 17% to 43.33% during 2017.- Social: We have noted an important development of opposite migration, as before the cultivation of Indian cannabis, migration flows from the Ghafsai region toward the cities, and the region quickly became a popular attraction for immigrants, as well as the spread of capitalist values (the spread of paid labor) at the expense of the inherent values of solidarity and cooperation represented by the Twiza phenomenon.On the environmental level, the cultivation of Indian cannabis negatively affects the environment through the degradation of the absentee field by uprooting and burning to expand the area of the air, the large water pumping of the fields, the erosion of the soil, etc. All of these factors lead to environmental imbalances in the region of Gefasai. This imposes: The State should develop economic projects to promote development in the region.The land resources of the region are to be valuable in order to create economic growth and to develop the soil.The legalizing of the cultivation of the kif, and its investment in the medical and industrial field.Establishment of economic and social cooperatives aimed at creating employment opportunities within this marginalized rural area.- Developing the infrastructure and Susioeconomic equipment in the Ghafsay region, making it a radiation pole and attracting investments, etc.
Keywords: Ghafsay; poverty; cannabis; environment; reverse migration